New asymmetric metal-catalysed addition processes for amine synthesis - Franchino, A (2017)
This thesis concerns the development of novel catalytic approaches for the construction of stereocentres bearing a nitrogen atom. In 2011, the Dixon group reported a Ag(I)/cinchona-derived amino phosphine catalytic system for the activation of isocyanoacetates in asymmetric aldol and Mannich reactions. During this thesis work it was sought to extend the scope of this catalytic system to Mannich additions of other isocyanide pronucleophiles, then the focus was broadened to include Reformatsky and α-alkylation reactions of ketimine substrates. Chapter 1 gives an overview of the state of the art with particular emphasis on catalytic enantioselective additions to ketimines and the use of activated isocyanides as pronucleophiles. Chapter 2 describes the application of the Ag-catalysed enantio- and diastereoselective aldol reaction of isocyanoacetates to the concise asymmetric synthesis of the antibiotic chloramphenicol, which possesses a chiral stereodefined α-amino β-hydroxy motif. Chapter 3 details our efforts to expand the scope of the Ag(I)/amino phosphine catalytic system to the activation of more challenging isocyanides lacking an electron-withdrawing group in the α-position by investigating aldol and Mannich reactions of benzyl isocyanide. Chapter 4 describes how the scope of the Ag(I)/amino phosphine catalytic system was successfully extended to another pronucleophile, the versatile p-toluenesulfonylmethyl isocyanide (TosMIC). The first catalytic enantio- and diastereoselective addition of TosMIC to N-diphenylphosphinoyl (N-DPP) ketimines was developed, affording 2-imidazolines possessing two contiguous stereocentres with high yields and excellent levels of stereocontrol. Chapter 5 describes the development of a Ni(II)-catalysed Reformatsky reaction of N-DPP ketimines with ethyl bromoacetate and diethylzinc, providing racemic amines bearing a quaternary stereocentre in the α-position in good yields. Chapter 6 reports the serendipitous discovery of the α-alkylation of N-DPP ketimines with ethyl bromoacetate using visible light photoredox catalysis. The transformation, catalysed by ruthenium(II) and nickel(II) complexes under mild conditions, was optimised, its scope assessed and the mechanism investigated.